Workforce composition, productivity and pay: the role of firms in wage inequality - Criscuolo, Chiara (OECD Economics Department Working Papers, 2020)
In many OECD countries, low productivity growth has coincided with rising inequality. Widening wage and productivity gaps between firms may have contributed to both developments. This paper uses a new harmonised cross-country linked employer-employee dataset for 14 OECD countries to analyse the role of firms in wage inequality. The main finding is that, on average across countries, changes in the dispersion of average wages between firms explain about half of the changes in overall wage inequality. Two thirds of these changes in between-firm wage inequality are accounted for by changes in productivity-related premia that firms pay their workers above common market wages. The remaining third can be attributed to changes in workforce composition, including the sorting of high-skilled workers into high-paying firms